2013
DOI: 10.1590/s1679-87592013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of macrozoobenthic community and trophic structure of a subtropical lagoon on southeastern Brazil's Atlantic coast

Abstract: The objective of this study was to investigate the macrobenthic community of two compartments of the Maricá-Guarapina lagoon system, along the coast of Rio de Janeiro, Brazil, in relation to its abiotic sediment factors. An additional discrimination between sites was made, wherever the macrophyte Typha domingensis was found. This vegetation supposedly represents a potentially important food source for consumers. Furthermore, the trophic pathways were analyzed functionally by means of stable isotope analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
2
2
0
1
Order By: Relevance
“…Our granulometric analysis indicated that the sandy fraction predominates in the study area, with grain diameters varying between poorly sorted medium and coarse sand. These results are consistent with those reported by Mazurek (2011) and Ricevuto et al (2013) for Lagoa de Maric a.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our granulometric analysis indicated that the sandy fraction predominates in the study area, with grain diameters varying between poorly sorted medium and coarse sand. These results are consistent with those reported by Mazurek (2011) and Ricevuto et al (2013) for Lagoa de Maric a.…”
Section: Discussionsupporting
confidence: 94%
“…Here, we observed epitoky in all months, which may be related to the fact that the temperature varied between 20°C and 31°C. These results are consistent with those reported by Mazurek (2011) and Ricevuto et al (2013) for Lagoa de Maric a. Sette et al (2013) reported that the recruitment period of A. succinea is continuous in the Pina Basin estuary (Brazil), which could be due to the stability of water temperatures in tropical environments given that they oscillate little over seasons, unlike those of temperate environments.…”
Section: Discussionsupporting
confidence: 92%
“…and ultimately can be used to support future conservation actions and management (Lindeman, 1942, Ricevuto et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…An ancillary ecological approach with substantial benefits is stable isotope (SI) analyses, and more specifically assessing isotopic ratios of carbon (δ 13 C) and nitrogen (δ 15 N), which represent the dietary sources and trophic position, respectively of an organism (Newsome et al, 2010;Peterson & Fry, 1987). Stable isotope analyses have also successfully been used to detect anthropogenic organic matter and investigate its dispersion and fate throughout trophic consumer groups, which is highly relevant for estuaries subject to the progressive intensification of anthropogenic pressures (Ricevuto, Vizzini, Lardicci, & Gomes, 2013;Vizzini & Mazzola, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Foram desenvolvidos trabalhos na plataforma continental de Ubatuba (SP) (Matsuura & Wada, 1994;Soares et al, 2002;Corbisier, 2006;Corbisier et al, 2006) e de Cabo Frio (RJ) (Corbisier, 2006;Corbisier et al, 2014;Soares et al, 2014); nas baías de Guanabara, Sepetiba e Ilha Grande (RJ) (Bisi et al, 2012); nos sistemas estuarianos de Itamaracá (PE) (Schwamborn et al, 2002), Cananéia (SP) (Nagata et al, 2015) e Mamanguape (PB) (Claudino et al, 2015); no ecossistema de manguezal na Baia de Sepetiba (RJ) (Lacerda et al, 1986); e em sistemas de lagoas costeiras (Aguiaro, 1999;Garcia et al, 2007;Ricevuto et al, 2013). Em estudos de alimentação, foram utilizados por Lacerda et al (1991) para o caranguejo de mangue Aratus pisoni, por Mantelatto et al (2002) (Amaral et al, 2015a).…”
Section: Introductionunclassified